Tinjauan Kuat Geser Tanah Lempung Menggunakan Kapur Sebagai Bahan Stabilisasi Dengan Variasi Diameter Butiran Tanah - Praboto, Lintang Bayu (2016)
Based on the research results Wiqoyah (2003) Tanon soil is clay. Percentage sieve No. 200 clay is at 94.13%, liquid limit (LL) = 88.03%, the plasticity index (IP) = 49.44%. Based on the system of the American Association Of State Highway And Transportation Officials (AASHTO), clay Tanon included into the group of A-7-5, and based on the classification of the Unified Soil Classification System (USCS) belong to the group CH ie inorganic clay with high plasticity. Based on the research above example that stabilization with lime can improve soil conditions, but so far it is not known how the effect of variations in the diameter of grain to the stabilization of the land. In this study conducted an experiment using a variety of soil particle diameter is through sieve No. 4, through sieve No. 30 and sieve No. 50, this is done to determine whether the grain diameter variations affect the physical and mechanical properties of the clay soil. In this study, the test was conducted on the physical properties of the soil mix and test the DST (Direct Shear Test) with the addition of lime amounted to 2.5% and 5% of the weight of the sample. Results of testing the physical properties of the soil mixture obtained water content, density (specific gravity), the liquid limit and plasticity index fell, while the value of plastic limit and shrinkage limit rose. Results of soil testing mixtures classified according to AASHTO system, including a group of A-7-5, while according to the system USCS, clay + lime 2.5% into the group CH and clay + lime 5% belong to the group MH. Results of testing the mechanical properties of testing standards and testing Proctor DST (Direct Shear Test), from Proctor standard test showed a decrease in weight of dry volume and the largest decline occurred in the land passes No. 50 + lime 5% by volume dry weight values of 1.062 g / cm3, for optimum water content largest increase occurred in soil sieve No. 4 at the limestone addition of 5% with the results of the optimum water content of 32.46%. The test results DST (Direct Shear Test) increase, the biggest increase occurred in the soil through sieve No. 4 at the limestone addition of 5% with a value of shear stress (τ) 0.677 kg / cm2.